Lafadz Musytarak Dinamisasi Dalam Rumah Makna - Ahmad Haromaini (Indonesian Journal of Arabic Studies, 2019)
As a medium of human communication, the role of language is very important for human life. Language helps him express what is in his mind that is applied in the language system, even though it is intrinsically arbitrary "which is like" but in order to establish good communication it must be agreed by the user community. In its journey, the development of language faces the dynamics of meaning possessed by lafadz which is a container of meaning. Does it mean one meaning or allows another meaning to represent the lafadz? Arabic linguistic discourse known as musytarak Study of lafadz musytarak becomes important and - for a interpreter - he becomes a parameter of his competence in understanding the content of the Qur'an and - for ushuliyyin - is a condition that must be fulfilled considering they will perform istinbath al-ahkam-urgen for language learning and the development of Arabic linguistic studies. This short article attempts to explore the basicly of the study of musytarak.